Blockchain in digital healthcare - Borah, Malaya Dutta; Moro Visconti, Roberto; Deka, Ganesh Chandra, 1969- (Boca Raton : Chapman & Hall/CRC Press, 2022)
"Health information about a patient is very critical, and currently, health records are saved in the databases controlled by individual users or organizations. As there are many malicious users, this information is not shared with other organizations due to security issues or data tampering. Blockchain can be used to securely exchange sensitive healthcare data that can be accessed by organizations sharing the same network in turn allowing doctors/practitioners to provide better care for patients. F ocuses on patient-centric applications of blockchain technology Covers e-health, telemedicine and m-health advances and perspectives D iscusses impact of Blockchains on smart healthcare and blockchained platforms on B2B, B2C interactions P rovides solutions to (some) healthcare bottlenecks Analyses networking digital platforms (considering blockchains as a peculiar form of network) Includes case studies of healthcare applications for a realistic strand on the subject This book is aimed primarily at postgraduates and researchers studying blockchain technology with focus on healthcare Informatics. Software developers will also find this book helpful"--
OCLC-licensed vendor bibliographic record.
Keywords: Medicine -- Data processing; Blockchains (Databases); HEALTH & FITNESS / General; COMPUTERS / Information Theory